2019
DOI: 10.3389/fmicb.2019.01966
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Interactions Dominate the Autoregulation of Escherichia coli Stringent Factor RelA

Abstract: Amino acid starvation in Escherichia coli activates the enzymatic activity of the stringent factor RelA, leading to accumulation of the alarmone nucleotide (p)ppGpp. The alarmone acts as an intercellular messenger to regulate transcription, translation and metabolism to mediate bacterial stress adaptation. The enzymatic activity of RelA is subject to multi-layered allosteric control executed both by ligands – such as “starved” ribosomal complexes, deacylated tRNA and pppGpp – and by indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…To separate the effects of (p)ppGpp production from the effects of (p)ppGpp degradation, we tested 351 synthesis-deficient SYNTH D264G mutants (Nanamiya et al, 2008) of C-terminally truncated Rel 352 variants (Figure 4A). The toxicity of the DRRM variant is abolished by the D264G mutation 353 demonstrating that it is, indeed, mediated by (p)ppGpp production and not, for example, through 354 inhibition of protein synthesis via competitive binding to ribosomal A-site (the latter non-enzymatic 355 mechanism of toxicity was shown for E. coli RelA CTD (Turnbull et al, 2019) Supplementary Figure S2). 363…”
Section: Toxicity Of B Subtilis δRrm Rel Is Mediated By (P)ppgpp Synmentioning
confidence: 95%
See 1 more Smart Citation
“…To separate the effects of (p)ppGpp production from the effects of (p)ppGpp degradation, we tested 351 synthesis-deficient SYNTH D264G mutants (Nanamiya et al, 2008) of C-terminally truncated Rel 352 variants (Figure 4A). The toxicity of the DRRM variant is abolished by the D264G mutation 353 demonstrating that it is, indeed, mediated by (p)ppGpp production and not, for example, through 354 inhibition of protein synthesis via competitive binding to ribosomal A-site (the latter non-enzymatic 355 mechanism of toxicity was shown for E. coli RelA CTD (Turnbull et al, 2019) Supplementary Figure S2). 363…”
Section: Toxicity Of B Subtilis δRrm Rel Is Mediated By (P)ppgpp Synmentioning
confidence: 95%
“…To purify untagged B. subtilis Rel we combined our protocols used for purification of E. coli RelA 424 (Turnbull et al, 2019) and T. thermophilus Rel (Van Nerom et al, 2019). (Figure 2).…”
Section: Purification Of Rna-free Untagged B Subtilis Rel Requires Smentioning
confidence: 99%
“…In a reconstituted biochemical system, the factor behaves similarly to E. coli RelA, i.e., it has very low synthesis activity by itself and is potently activated by the ribosome. Conversely, deletion of the RRM domain in factors that naturally possess it leads to inhibition of growth (Gratani et al, 2018;Ronneau et al, 2019;Turnbull et al, 2019) that is mediated by over-production of (p)ppGpp in the cell, as shown for Caulobacter crescentus Rel (Ronneau et al, 2019) and E. coli RelA (Turnbull et al, 2019). The exact molecular mechanism of misregulation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The activation by initiation complexes was compromised, but not abrogated, and the synthetic activity of the Rel ΔRRM alone was weaker than that of the wild type. These results are seemingly at odds with mis-regulation and over-production of (p)ppGpp by both Rel ΔRRM (19) and RelA ΔRRM (32) in live cells, which could be attributed to the loss of autoinhibition in the mutant protein (15,18,44). This interpretation is not supported by our biochemical results, and follow-up experiments established that the toxicity of both B. subtilis Rel ΔRRM and E. coli RelA ΔRRM is strictly dependent on the interaction with starved ribosomes (31).…”
Section: Resultsmentioning
confidence: 98%
“…All bacterial strains and plasmids used in this study are listed in Supplementary Tables 1 and 2 . All proteins were expressed, purified and characterised using SUMO-tagging strategy described earlier for E. coli RelA (32) and B. subtilis Rel (31); gel filtration profiles for mutant Rel variants are shown as ( Supplementary Figure S1 ). Radiochemistry experiments were performed as described for E. coli RelA (13), with modifications.…”
Section: Methodsmentioning
confidence: 99%